2015
DOI: 10.1139/cjm-2015-0213
|View full text |Cite
|
Sign up to set email alerts
|

Development of an indirect ELISA based on a truncated S protein of the porcine epidemic diarrhea virus

Abstract: Porcine epidemic diarrhea (PED) is a highly contagious, enteric disease of swine caused by the porcine epidemic diarrhea virus (PEDV). To find a suitable ELISA method to assess the infection of PEDV and the effectiveness of vaccines, we developed and evaluated an indirect enzyme-linked immunosorbent assay (iELISA) based on a truncated recombinant spike (S) protein expressed in Escherichia coli. The parameters of the iELISA were optimized, and the cutoff value determined as 0.259 by analyzing optical density (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…Immunoperoxidase monolayer assay (IPMA), however, can detect the presence of the virus as early as 6dpi (Z. and offers the ability to verify the result not only by quantity (titre), but also be quality (specificity of the staining). While earlier indirect ELISAs were based on whole virus preparations (Knuchel et al, 1992;Oh et al, 2005), more recently developed indirect ELISA's are based on recombinant forms of viral membrane, N or S proteins (Fan et al, 2015;Hou et al, 2007;Li et al, 2015). Alternatively blocking ELISA's are used and have been postulated to have greater levels of specificity and sensitivity when compared with other assays (van Nieuwstadt and Zetstra, 1991;Carvajal et al, 1995).…”
Section: Challenges For the Control Of Pedvmentioning
confidence: 99%
“…Immunoperoxidase monolayer assay (IPMA), however, can detect the presence of the virus as early as 6dpi (Z. and offers the ability to verify the result not only by quantity (titre), but also be quality (specificity of the staining). While earlier indirect ELISAs were based on whole virus preparations (Knuchel et al, 1992;Oh et al, 2005), more recently developed indirect ELISA's are based on recombinant forms of viral membrane, N or S proteins (Fan et al, 2015;Hou et al, 2007;Li et al, 2015). Alternatively blocking ELISA's are used and have been postulated to have greater levels of specificity and sensitivity when compared with other assays (van Nieuwstadt and Zetstra, 1991;Carvajal et al, 1995).…”
Section: Challenges For the Control Of Pedvmentioning
confidence: 99%
“…Subsequently, it has been confirmed that the PEDV CHGD-01 variant strain exhibits stronger sugar-binding activity than the CV777 prototype strain, suggesting that the mutated amino acids may participate in sugar binding, and the authors also proposed that the enhanced sugar-binding activity of the variant strains may be responsible for the recent PED outbreaks [19]. Furthermore, in an indirect ELISA based on NTD (tSc, aa 25-225) of PEDV S1 domain showed positive correlations between OD values of pig sera and virus neutralization titers [20]. Therefore, the NTD of PEDV S1 domain may have potential to be used as a subunit vaccine against PEDV variant strains.…”
Section: Introductionmentioning
confidence: 98%
“…Since PEDV has become widespread in pig herds worldwide, many methods, such as RT-PCR [9], duplex RT-PCR [12], immunofluorescence analysis, immunohistochemical analysis, in situ hybridization [11], RT-loop-mediated isothermal amplification [21], and indirect ELISA, have been established to monitor viruses and antibodies [4,6,15]. However, the above-mentioned methods are time-consuming and are mainly limited to use in the lab, with the exception of the ICA kit [18].…”
Section: Discussionmentioning
confidence: 99%